If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(6a + -9) = 0 Reorder the terms: 4(-9 + 6a) = 0 (-9 * 4 + 6a * 4) = 0 (-36 + 24a) = 0 Solving -36 + 24a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + 24a = 0 + 36 Combine like terms: -36 + 36 = 0 0 + 24a = 0 + 36 24a = 0 + 36 Combine like terms: 0 + 36 = 36 24a = 36 Divide each side by '24'. a = 1.5 Simplifying a = 1.5
| 6.6x-5+x-1.7= | | -3+x=6 | | 3n-31=2 | | 3x-2x+9=6 | | 3(x-4)+5=x-15 | | 10-6n=-14 | | -3*x=6 | | y=-10/5+1 | | 10-6n=-4 | | m^4-5m^3+7m^2-3m=0 | | 6-(4x-2)=3-5x | | 2xy-xz=0 | | x+(-3)=-14 | | 2x^2-28x-64=0 | | 3x+5x=7x+9 | | -6+7x=0 | | 10y+6=8y-8 | | ln(-6+7x)=0 | | 3x^2+13x+22=0 | | 3(2a+15)-8a=-11 | | 6x-6=4x+42 | | 3(x+3)=-15 | | 50x^3+175x^2-8x-28=0 | | 45-2x=x+30 | | mn+16=4 | | 5x^2-120=5 | | 3(4x+8)=9x+12 | | 45-3x=-8x | | -2(-2b+5)8b=14 | | m+16=4 | | y=3(-24)-6 | | x^2+14x-5k+4k^3+1=0 |